Unpacking Johannesburg's international city-to-city partnerships. - Buxbaum, Galia (My University, 2014)
In this era of globalisation and rapid urbanisation, can city-to-city partnerships provide a unique approach towards contributing to the development needs of South African cities? There is a growing literature dedicated to North-South and South-South municipal international cooperation, exploring impacts on local governance and development, for either or both of the cities. However, there is a paucity of knowledge on this topic in South Africa. This project hopes to address this critical occlusion by examining Johannesburg’s experience of city-to-city cooperation partnerships. These partnerships will be examined with reference to how they are organised and their implementation. Has cooperation provided social and economic development in Johannesburg as agreements often state? To answer the research questions, an in-depth understanding of city-to-city partnerships in South Africa is required; therefore a qualitative data collection approach was adopted. City-to-city cooperation crosses geographical borders, and this study investigates how it also extends across theories, government spheres and topics. The research traces policy and practice of international city-to-city cooperation relationships, identifying the salient aspects of these city-level engagements and incorporates a critical view of policy documents that frame municipal international relations in South Africa, specifically in Johannesburg. The research shows that international city-to-city cooperation agreements should be greeted with a degree of scepticism in terms of the disparity between the agreement’s objectives, and the practical experience of implementation. Municipal international relations are an interesting exercise in city autonomy in the global economy, yet they are often conscribed by provincial and national government requirements.
Keywords: City-to-city cooperation; Municipal international relations; Twin city; Sister city; Globalisation; Development; Local government; Global South; City of Johannesburg